Riding On The Winds Of Change: Transforming Marine Warranties Into Lesser Contractual Terms - Tharmakulasingam, Sri Ganesan (Journal of Malaysian and Comparative Law, 2019)
A breach of warranty has drastic consequences. When a breach of warranty occurs, the insurer is automatically discharged from liability. In many countries, the war against this draconian remedy has begun. In Australia, the Australian Law Reform Commission in its Report No. 91 on The Review of the Marine Insurance Act 1909, recommended reforms in many areas of marine iinsurance and warranties were on top of the reform list, where the Commission recommended the abolition of this concept. A similar trend is also seen in Canada. In the United Kingdom statistics show that the marine insurance market in London has been under significant threat for some time. The London market has lost its market share of the world marine insurance business due to the intense competition from France, Germany, Switzerland, Italy, Scandinavia, the USA and especially Norway. Many of these alternative markets were able to offer marine insurance cover on the lowest available market rate and on the best possible terms. Norwegian law does not have the concept of warranties. To remain competitive and to regain lost market share the IHC 2002 was introduced in the UK. These clauses have been viewed as more consumer-friendly, as there appears to be a draft away from the use of insurance warranties in these clauses.